MOTIVATION OF STUDENTS TO LEARN: SOCIAL AND PSYCHOLOGICAL ASPECT - N. Gerasimenko (Publishing House of the State University of Management, 2017)
Now a serious social and psychological problem of motivation to training is the fact that students «at any cost» and on any terms are necessary for higher education institutions. Article is devoted to problems of studying of educational motivation of students. In it the used terms «motive» and «motivation» are analyzed and also results of an empirical research of motivation of students of the Russian higher education institutions are presented, some recommendations for students and teachers for the purpose of increase in educational motivation and, respectively, growth of effectiveness of process of training are formulated.